2022
DOI: 10.1038/s41598-022-26231-w
|View full text |Cite
|
Sign up to set email alerts
|

Vagus nerve stimulation attenuates acute kidney injury induced by hepatic ischemia/reperfusion injury in rats

Abstract: Hepatic ischemia/reperfusion (I/R) injury, caused by limited blood supply and subsequent blood supply, is a causative factor resulting in morbidity and mortality during liver transplantation and liver resection. Hepatic I/R injury frequently contributes to remote organ injury, such as kidney, lung, and heart. It has been demonstrated that vagus nerve stimulation (VNS) is effective in remote organ injury after I/R injury. Here, our aim is to investigate the potential action of VNS on hepatic I/R injury-induced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Furthermore, proteomic analysis revealed that plasma glutathione and glutathione peroxidase levels were significantly increased by VNS, implying that the protective effect may be related to glutathione metabolism. Furthermore, VNS can also protect distal organs against hepatic IR-induced injury, such as the lung, kidney and skeletal muscle [ [155] , [156] , [157] ]. Currently, there are no clinical trials examining the effect of VNS on hepatic IRI patients, and further studies are needed to confirm its effectiveness.…”
Section: Vns Plays a Protective Role In Iri Of Different Organsmentioning
confidence: 99%
“…Furthermore, proteomic analysis revealed that plasma glutathione and glutathione peroxidase levels were significantly increased by VNS, implying that the protective effect may be related to glutathione metabolism. Furthermore, VNS can also protect distal organs against hepatic IR-induced injury, such as the lung, kidney and skeletal muscle [ [155] , [156] , [157] ]. Currently, there are no clinical trials examining the effect of VNS on hepatic IRI patients, and further studies are needed to confirm its effectiveness.…”
Section: Vns Plays a Protective Role In Iri Of Different Organsmentioning
confidence: 99%
“…Subsequent research has increasingly suggested that VNS can also confer protection against heart failure progression, due to the restoration of autonomic balance, baroreceptor sensitivity, and electrical stability ( Capilupi et al, 2020 ; Verrier et al, 2022 ; Elamin et al, 2023 ). Recent studies have progressively unveiled the role of VNS in mitigating myocardial I/R injury through the activation of the cholinergic anti-inflammatory pathway, anti-oxidative stress response, or anti-apoptotic response ( Chen et al, 2020 ; Wang et al, 2020 ; Deng et al, 2022 ). However, the intricate mechanisms underlying VNS-mediated cardioprotection in experimental studies, along with limited clinical evidence, pose obstacles to its broader application in clinical practice.…”
Section: Introductionmentioning
confidence: 99%